PENYULUHAN TENTANG PENERAPAN ROLL O’PACK DI RUANG PENYIMPANAN REKAM MEDIS DI RUMAH SAKIT UMUM SEMBIRING - Rusdi Andreas Sembiring; Jon Piter Sinaga (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The confidentiality of the contents of medical records is strengthened by the Republic of Indonesia Minister of Health Regulation No. 269 / Menkes / Per / III / 2008 article 10 paragraph 1 which states "Information about the identity, diagnosis, medical history, examination history and treatment history of the patient must be kept confidential by doctors, dentists, certain health workers, management officers and leaders of service facilities. Health ”The medical record file storage system in public hospitals while using a centralized management system where outpatient and inpatient medical record files become one. The storage device uses an open wooden shelf. According to the Ministry of Health, RI (1991) in Ahmadi (2011: 16), that the medical record file storage room must pay attention to the following matters: The medical record storage room should be separated from other office rooms to maintain the safety of these medical records. Roll O Pack is a Push Filing cabinet for storing large capacity documents that can be moved manually or by mechanical drive. The results showed that before conducting counseling, the officers did not know the advantages and disadvantages of using the o'pack roll, before implementing the o'pack roll at the RSU Sembiring, the officer had to know first what the advantages and disadvantages of the o'pack roll were, if the o'pack roll gave more There are many advantages for officers and services, so the implementation of roll o'pack is very much needed and must be realized as soon as possible so that the storage system at the RSU Sembiring becomes rapid and the files are not damaged so that the useful value of medical record files is better.